Determinants of Consumer Purchase Intention and Behavior toward Green Product: The Moderating Role of Price Sensitivity - Zinoubi, Zohra Ghali (Archives of Business Research, 2020)
The purpose of the current study is to investigate a set of determinants favoring the green purchase intention and behavior. The literature review enabled us to mostly distinguish the following determinants: perceived consumer effectiveness, health consciousness, and social influence. The moderating role of price sensitivity is also examined. The Structural Equation Modelling (SEM) was used to test the research hypotheses. The findings of a quantitative study involving 320 consumers of green products indicated positive and significant impacts of these three motives on consumer purchase intention. However, they have weak direct impacts on consumer behavior. Full mediating roles of green purchase intention were confirmed between perceived consumer effectiveness, health consciousness, social influence and consumer behavior. The positive relationship between green purchase intention and behavior was found inversely influenced by consumer price sensitivity. The present study provides managerial insights for green marketers in order to boost green consumption in developing markets.